Telnesgården, an historic home in Tromsø, Norway ... - Campbell, Sandy (University of Alberta Library, 2024)
This historic home, Telnesgården, in Tromsø, Norway was built in approximately 1865. It was occupied initially by a master shoemaker, Hans Løkke, then a master painter, A. Larsen, and a cathedral organist, Helmer Telnes. Polar explorer Hjalmar Johansen rented this house in 1903. The exterior is covered with vertical wood paneling that is painted orange. The window trim is dark green. There are two smaller outbuildings behind the house. ...